Accuracy of Gaussian approach for the performance evaluation of direct-detection receiver with partially polarized noise - Rebola, J. (2022)
We investigate the accuracy of a Gaussian approach (GA) developed to estimate the performance of a direct-detection optical receiver with arbitrary optical and electrical filtering and in the presence of partially polarized noise due to polarization-dependent loss (PDL). The accuracy is assessed by comparison of the performance estimates obtained from the GA with the estimates obtained from a rigorous method (RM) based on the calculation of the moment-generating function of the current at the optical receiver output. We show that the GA has a good accuracy when considering the variation of the optical filter bandwidth, extinction ratio, degree of polarization of the noise (DOP), and angle between signal and noise polarizations. However, it fails to predict the receiver sensitivity within 2 dB of the RM when DOP is greater than 0.7 and signal and noise polarizations are orthogonal in the Jones space. Nevertheless, it is shown that the GA provides receiver sensitivity estimates with good accuracy in most cases of long-haul optical communication systems influenced by PDL, where the typical average DOP is below 0.15. Due to its simplicity, shorter computation time, and good accuracy, the GA is a good tool to assess the performance of such optical systems.